Mediated mimbar: muslim media and identity in Uganda - Nsobya, Abdulhakim (Department of Religious Studies, 2025)
Motivated by the scarcity of literature on the relationship between Muslims and media in East Africa, and Uganda in particular, this thesis examines the transformative role of new media in shaping the Islamic identity in Uganda. Since the liberalization of media in 1992, Ugandan Muslims have increasingly adopted new media, integrating it into their daily lives and religious practices. The study argues that new media has become a crucial platform for negotiating Islamic identity, serving as space where power, representation, and religious expression are contested and redefined. Drawing on interviews with media practitioners, scholars, and media consumers, the study has explored the motivations, strategies, and attitudes, that guide Muslims in their engaged with new media. Historically, Ugandan Muslims relied on the mosque Minbar and religious festivals as primary avenues for communication, particularly to express social and economic grievances. With limited access to the national broadcaster, these traditional platforms were essential for intra-faith debate and theological discourse. However, the advent of new media has significantly altered this landscape. New media now functions as a powerful tool for addressing issues of misrepresentation and marginalisation, providing a discursive space for diverse and often conflicting views within the Muslim community. The study highlights the rise of Salafism as a dominant voice in Ugandan media, using new theology to promote its theological perspective while rejecting opposing views. Additionally, radical groups like Allied Democratic Forces (ADF) have leveraged social media to reach a broader audience, bypassing traditional media gate keepers. This thesis contributes to the academic study of religion and media by offering an in-depth analysis of how new media facilitate the articulation of Islamic identity in Uganda. It underscores the importance of new media as a site of power struggles among reformists, traditionalist, modernists, and radical factions within Islam, each striving to shape the narrative and influence the future of the faith in Uganda.